Review, Gratis Ongkir dan Pembayaran Non Tunai (Shopeepay Later ) terhadap Keputusan Pembelian Marketplace Shopee di Kota Medan - Maisara Batubara; Vincent Genesius Beltham; Marshella Valencia Salim; Tarynie Audriya; Atika Aini Nasution (Journal of Management and Bussines (JOMB), 2024)
This research was motivated by the aim of testing and analyzing the influence of reviews, free shipping and non-cash payments on purchasing decisions for the Shopee Marketplace in Medan City among students at the Faculty of Law, Prima Indonesia University. This research method uses quantitative. The total population is all students from the Faculty of Law at Prima Indonesia University with a sample of 97 students. The sampling technique used is non-probability sampling. The results of partial hypothesis testing show that reviews with tcount > ttable (2,251>1,985), free shipping (6,822>1,985), and non-cash payments (2,213>1,985) have a significant influence on purchasing decisions at Shopee Marketplace in Medan City. The results of simultaneous hypothesis testing show that reviews, free shipping, and non-cash payments have a significant influence on purchasing decisions for the Shopee Marketplace in Medan City with a value of Fcount > Ftable (47,848 > 3.09) and a significance of 0.000. Keywords: Free Shipping, Purchase Decision, Non-Cash Payment